Diseño de un modelo de gestión del talento humano por competencias de la empresa Ekuaflor, período 2018 - Agila Condoy, Nelson Ramiro (2018)
Abstract: The present work of titration, called: "design of model management of the human talent by competencies Ekuaflor s company, period 2018", is of great importance for the organization, since it allows him establish a suitable process of management by competitions and therefore a greater business development that means a competitive advantage in front of other companies of the same sector.. With this proposal looks for improve the taking of decisions, so that these make of technical way, taking in account points of view wider and detailed, implementing a model of management adapted. For this purpose a descriptive investigation was carried out, based on the inductivedeductive methods and Analysis; In addition to a direct observation based on the application of a Focus Group, to improve the results. With all the information that obtained, could determine which were the suitable competitions for each charge of the organization and attained establish the necessary contours for a optimal management of the human tallent.